Advancing public health through technological rehabilitation: insights from a national clinician survey - Marianna Capecci; Marialuisa Gandolfi; Sofia Straudi; Rocco Salvatore Calabrò; Nicolò Baldini; Lucia Pepa; Elisa Andrenelli; Nicola Smania; Maria Gabriella Ceravolo; Giovanni Morone; Donatella Bonaiuti; on behalf of HTA section of SIMFER (Italian Society of Physical and Rehabilitation Medicine) (BMC Health Services Research)
Abstract Introduction In the evolving healthcare landscape, technology has emerged as a key component in enhancing system efficiency and offering new avenues for patient rehabilitation. Despite its growing importance, detailed information on technology's specific use, types, and applications in clinical rehabilitation settings, particularly within the Italian framework, remains unclear. This study aimed to explore the use of technology and its needs by Physical Medicine and Rehabilitation medical doctors in Italy. Methods We conducted a cross-sectional online survey aimed at 186 Italian clinicians affiliated with the Italian Society of Physical and Rehabilitation Medicine (SIMFER). The online questionnaire consists of 71 structured questions designed to collect demographic and geographical data of the respondents, as well as detailed insights into the prevalence and range of technologies they use, together with their specific applications in clinical settings." Results A broad range of technologies, predominantly commercial medical devices, has been documented. These technologies are employed for various conditions, including common neurological diseases, musculoskeletal disorders, dementia, and rheumatologic issues. The application of these technologies indicates a broadening scope beyond enhancing sensorimotor functions, addressing both physical and social aspects of patient care. Discussion In recent years, there's been a notable surge in using technology for rehabilitation across various disorders. The upcoming challenge is to update health policies to integrate these technologies better, aiming to extend their benefits to a wider range of disabling conditions, marking a progressive shift in public health and rehabilitation practices.